Das Körperwachstum bei Blattläusen (Homoptera, Aphididae) als Ausdruck des Nährstoffangebots in der Wirtspflanze. Teil II. Untersuchungen an Stielen abgeschnittener Blätter von Tropaeolum majus L. - Scholze, Peter (Contributions to Entomology = Beiträge zur Entomologie, 1992)
On stems of excised leaves of Tropaeolum majus L. nutritive effects of the host plant on the postnatal development of the black bean aphid, Aphis fabae ssp. mordvilkoi Börner & Janisch, is demonstrated. Weight gain (mg x) of six days old apterous exules was used as a criterion for growth. Progress in aphids' body weight depends on amounts of nitrogen and carbohydrate containing nutrients, which are formed during ageing process of leaves and then translocated in the stem. Greater senescing leaves cause higher average weights then smaler ones. Application of kinetin (6-Furfurylaminopurine) on leaves to prevent protein breakdown retards the progress in body weight. After mechanical cutting phloem elements through a dumming up of nutrients arises and growth of aphids accelerates. The differentiation of nutrient supply in the stems is shown to be expressible in a quantitatively identical manner with the mean weight of the aphids.